Effects of Low- and High-Frequency Side Bands of Notched Noise on Masking and Auditory Filter Shape at Very High Frequencies - KORDUS, Monika; KOWALEWSKI, Borys (Archives of Acoustics, 2015)
This paper is concerned with the determination of the auditory filter shape using the notched noise method with noise bands symmetrically located above and below a probe frequency of 10 kHz. Unlike in the classical experiments conducted with the use of Patterson method the levels as well as power spectrum densities of the lower and upper component bands of the notched noise masker were not the same and were set such as to produce the same amount of masking at the 10-kHz frequency. The experiment consisted of three conditions in which the following values were determined: (I) the detection threshold for a 10-kHz probe tone in the presence of a noise masker presented below the tone’s frequency; (II) the level of a noise masker presented above the 10-kHz probe tone frequency, at which the masker just masked the probe tone, (III) the detection threshold for a probe tone in the presence of a notched-noise masker. The data show a considerable amount of variability across the subjects, however, the resulting frequency characteristics of the auditory filters are consistent with those presented in the literature so that the Equivalent Rectangular Bandwidth is less than 11% of their centre frequency.